Analisis Peningkatan Performa Dosen Menggunakan Konsep Job Demand-Control Support - M. Yusuf Alfian Rendra Anggoro KR; Harun Samsudin; Samsul Akmal; Pandu Adi Cakranegara; Abdurohim Abdurohim (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of work stress which includes role conflict and workload on employee performance, especially at university lecturers in Banten. Respondents in this study were 106 lecturers from 13 universities in Banten. Data analysis using multiple linear regression with the help of the SPSS 20 program. The results of this study indicate that workload has a negative and significant effect on employee performance, but role conflict has a negative and not significant effect on employee performance. Simultaneously, role conflict and workload have a significant effect on employee performance. The implication of this research is expected to provide information and input to relevant institutions (university leaders), especially universities in Banten in their efforts to minimize the impact of negative work stress on employee performance.